The grapevine NIP2;1 aquaporin is a silicon channel - Noronha, Henrique Luís Silva (2020)
Silicon (Si) supplementation has been shown to improve plant tolerance to different stresses, and its accumulation in the aerial organs is mediated by NIP2;1 aquaporins (Lsi channels) and Lsi2-type exporters in roots. In the present study, we tested the hypothesis that grapevine expresses a functional NIP2;1 that accounts for root Si uptake and, eventually, Si accumulation in leaves. Own-rooted grapevine cuttings of the cultivar Vinhao accumulated >0.2% Si (DW) in leaves when irrigated with 1.5 mM Si for 1 month, while Si was undetected in control leaves. Real-time PCR showed that VvNIP2;1 was highly expressed in roots and in green berries. The transient transformation of tobacco leaf epidermal cells mediated by Agrobacterium tumefaciens confirmed VvNIP2;1 localization at the plasma membrane. Transport experiments in oocytes showed that VvNIP2;1 mediates Si and arsenite uptake, whereas permeability studies revealed that VvNIP2;1 expressed in yeast is unable to transport water and glycerol. Si supplementation to pigmented grape cultured cells (cv. Gamay Freaux) had no impact on the total phenolic and anthocyanin content, or on the growth rate and VvNIP2;1 expression. Long-term experiments should help determine the extent of Si uptake over time and whether grapevine can benefit from Si fertilization.